The T-lymphocyte population in first-trimester human decidua does not express the interleukin-2 receptor. - Bulmer, J N (1986)
The expression of the IL-2 receptor by T lymphocytes in human uterine decidua has been studied with two monoclonal antibodies to the IL-2 receptor employed in immunoperoxidase labelling of serial cryostat sections. Infiltrating T lymphocytes in early pregnancy decidua do not express the IL-2 receptor. Endometrial gland epithelium in early pregnancy showed unexpected reactivity with one of the mAbs to the IL-2 receptor (Tac). Thus, despite the close proximity of fetal trophoblast, macrophages and T-lineage lymphocytes in decidua in early pregnancy, IL-2 receptor-bearing lymphocytes are completely absent.